Caribbean coral reef fishery resources bibliography (Ministry of Agriculture, Land and Marine Resources Port of SpainTT, 1992)
Consists of two separate bibliographies - the first is a collection of references from the Fisheries Division's 'stock' database, and the second is a collection of related references from the CD-Rom version of Aquatic Sciences and Fisheries Abstracts (ASFA) up to December 1991, not present in 'stock'. Pays special attention to the exploited families Lutjanidae, Serranidae, Haemulidae and Palinuridae.
Bibliography was prepared for the CARICOM consultation